Orodispersible Tablets: A Compendious Review - Roshan, Kenneth; Keerthy, H.S (Asian Journal of Pharmaceutical Research and Development, 2021)
In recent times, there has been an enhanced demand for more patient compliant dosage forms. Oral route has been the gold standard in the administration of medications due to its safety, good patient compliance, ease of ingestion, pain avoidance and versatility. Dysphagia poses a problem especially in geriatric and paediatric patients. Mentally retarded patients, institutionalized patients and those travelling without access to water face a challenge as well. Orodispersible tablets are solid unit dosage form which when placed in the oral cavity swiftly disintergrates or dissolves without the need of water. ODT technology helps overcome the above mentioned challenges. Literature on ODT, their formulation and evaluation, challenges, manufacturing techniques along with patented technologies are reviewed in this article.